2020
DOI: 10.1108/ijchm-05-2020-0402
|View full text |Cite
|
Sign up to set email alerts
|

Is TripAdvisor still relevant? The influence of review credibility, review usefulness, and ease of use on consumers’ continuance intention

Abstract: Purpose Recent figures show that users are discontinuing their usage of TripAdvisor, the leading user-generated content (UGC) platform in the tourism sector. Hence, it is relevant to study the factors that influence travelers’ continued use of TripAdvisor. Design/methodology/approach The authors have integrated constructs from the technology acceptance model, information systems (IS) continuance model and electronic word of mouth literature. They used PLS-SEM (smartPLS V.3.2.8) to test the hypotheses using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 111 publications
2
86
0
2
Order By: Relevance
“…Thus, food tourism is worthwhile to investigate beyond regular restaurant consumption. More specifically, the increase in the usage of social media, such as TripAdvisor, requires research on eWOM behavior, that is, the behavior of sharing and spreading information regarding dining experiences during travel with strangers worldwide (Filieri et al, 2021;Line et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, food tourism is worthwhile to investigate beyond regular restaurant consumption. More specifically, the increase in the usage of social media, such as TripAdvisor, requires research on eWOM behavior, that is, the behavior of sharing and spreading information regarding dining experiences during travel with strangers worldwide (Filieri et al, 2021;Line et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the credibility of online platforms and tourism businesses is jeopardized. Low credibility will weaken consumers’ continuance intentions and hinder the development of online businesses (Chakraborty, 2019; Filieri et al , 2021; Law et al , 2020). Therefore, fake reviews must be identified in website and business management.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, information communication technologies have a decisive influence on the competitiveness of tourism organizations and destinations and on the tourism system itself. They enable tourists to exchange information about tourist attractions and services, thus influencing other tourists' decisions about where to go and which services to choose [46][47][48][49][50]. Evidently, the BN monthly user-generated content about the South Baltic sites plays an important role and therefore should be utilized in the sustainable management strategies.…”
Section: Discussionmentioning
confidence: 99%